ANALISIS SEKTOR BASIS DAN SEKTOR NON BASIS SEBAGAI PENENTU POTENSI UNGGULAN DI KOTA SURAKARTA TAHUN 2010-2014 (Lembaga Pengembangan Kinerja Dosen, 2022)
Economic development needs to be driven continuously to support economic growth in an area. One of the components that can be seen from economic growth is GRDP data. In this research, the author conveys that the results of the calculation are to detect the base sector and the non-base sector in the Surakarta City area so that superior sectors can be found as drivers of economic growth. the application of the method in this calculation is the Location Quotient (LQ) analysis method as well as the Dynamic Location Quotient (DLQ) as a determinant that the sector is able to develop in the future or not. With the initial data used as a comparison, namely GRDP data according to the Usha Field of Surakarta City with GRDP data according to the Central Java Province USAHA Field. The results of the LQ calculation show that the Information and Communications sector is in the first position with the highest average LQ value among other sectors, namely 3.3. While the results of the DLQ calculation say that all sectors have the potential to develop in the future.